A New Life Down Under B.2 - Boonstra, Jean; Nang Chan Yeema (Nampa, ID USA Pacific Press Publishing Association, 2004)
Heather now has a happy new outlook on life. At year's end, the message of hope makes Heather long for heaven. A very special baptism follows at Dora Creek. She wants to follow Jesus; she discovers the joy of having Him in her heart and sharing Him with others.
Keywords: Story Collection